The Role of the Principal in Developing a Literacy Culture: A Qualitative Study at SDN Brebes 09, Brebes Regency - Hardiman, Sofandy; Nurkolis, Nurkolis; Kusumaningsih, Widya (FKIP - Universitas Riau, 2025)
Low literacy achievement in Indonesia, as reflected in national and international assessments, underscores the urgency of strengthening literacy culture in schools. This study analyzes the role of the school principal in developing literacy culture at SDN Brebes 09, Brebes Regency. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation. The findings show that the principal performs three crucial roles: educator, motivator, and innovator. As an educator, the principal integrates literacy into daily learning, guides teachers, and models literacy practices. As a motivator, the principal fosters a supportive school climate, provides recognition, and conducts regular evaluations of literacy programs. As an innovator, the principal initiates creative programs such as Radigabluk (Rajin Membaca dan Menulis Buku), establishes reading corners, and engages parents in literacy activities. These efforts enhance students’ reading interest, increase writing output, and strengthen teacher and parent involvement. The impact is evident in improved 2022–2023 Education Report scores and the BOS Kinerja award. The study concludes that principal leadership, through educational, motivational, and innovative roles, is pivotal in cultivating sustainable literacy culture in elementary schools.